VALUE PRIORITIES OF EDUCATION OF KAZAKHSTAN IN THE CONTEXT OF GLOBALIZATION OF HIGHER EDUCATION - Khassanov, M. Sh.; Petrova, V. F.; Shaidulina, D. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
The paper discusses the value of national development in the light of «Kazakhstan’s way – 2050». It is noted that changes in education are inextricably linked to the processes taking place in the sociopolitical and economic life of the world community, when the world’s leading trend is the globalization of social and cultural processes. It is indicated that the value of national education should be the same as the value of the national economy. These include independence, national unity, peace and harmony in Kazakhstan society, secular society and high spirituality, common history, culture and language. Key words: value, education, harmony, unity, people, culture, language.